PENGARUH BRAND AMBASSADOR, HALAL AWARENESS, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK HALAL PRIA DI E-COMMERCE - Haris Sutanto (2023)
The trend of using men's cosmetics is currently increasing, this can be seen from the market share of beauty and skin care products in e-commerce which reaches 43,5%, but related to halal awareness of using cosmetics, men are less concerned about halal awareness when compared to women . Moreover, the trend of using brand ambassadors as company representative products is considered less effective in influencing consumer purchasing decisions. This study aims to explain the influence of brand ambassadors, halal awareness, and product quality on purchasing decisions for men's halal cosmetics. The population of this study was the Muslim community of DKI Jakarta who use halal cosmetics. Sampling method using non-probability sampling technique with purposive sampling method. The approach used is quantitative. Questionnaires are used as data collection techniques. Partial Least Square is used as a data analysis technique. The data test uses the outer and inner models. The results showed that the brand ambassador have a significant influence to purchasing decisions. Meanwhile, halal awareness and product quality variables has no significant influence to purchasing decisions.